Identification, Mapping, and Genetic Diversity of Novel Conserved Cross-Species Epitopes of RhopH2 in Plasmodium knowlesi With Plasmodium vivax - Ahmed, Md Atique; Deshmukh, Gauspasha Yusuf; Zaidi, Rehan Haider; Saif, Ahmed; Alshahrani, Mohammed Abdulrahman; Wazid, Syeda Wasfeea; Patgiri, Saurav Jyoti; Quan, Fu-Shi (Frontiers in Cellular and Infection Microbiology, 2022)
Malaria is a major public health concern, and any tangible intervention during the pre-elimination phase can result in a significant reduction in infection rates. Recent studies have reported that antigens producing cross-protective immunity can play an important role as vaccines and halt malaria transmission in different endemic regions. In this study, we studied the genetic diversity, natural selection, and discovered novel conserved epitopes of a high molecular weight rhoptry protein 2 (RhopH2) in clinical samples of Plasmodium knowlesi and Plasmodium vivax cross-protective domains, which has been proven to produce cross-protective immunity in both species. We found low levels of nucleotide diversity (P. knowlesi; π ~ 0.0093, SNPs = 49 and P. vivax π ~ 0.0014, SNPs = 23) in P. knowlesi (n = 40) and P. vivax (n = 65) samples in the PkRhopH2 cross-protective domain. Strong purifying selection was observed for both species (P. knowlesi; dS - dN = 2.41, p < 0.009, P. vivax; dS - dN = 1.58, p < 0.050). In silico epitope prediction in P. knowlesi identified 10 potential epitopes, of which 7 epitopes were 100% conserved within clinical samples. Of these epitopes, an epitope with 10 amino acids (QNSKHFKKEK) was found to be fully conserved within all P. knowlesi and P. vivax clinical samples and 80%–90% conservation within simian malaria ortholog species, i.e., P. coatneyi and P. cynomolgi. Phylogenetic analysis of the PkRhopH2 cross-protective domain showed geographical clustering, and three subpopulations of P. knowlesi were identified of which two subpopulations originated from Sarawak, Malaysian Borneo, and one comprised only the laboratory lines from Peninsular Malaysia. This study suggests that RhopH2 could be an excellent target for cross-protective vaccine development with potential for outwitting strain as well as species-specific immunity. However, more detailed studies on genetic diversity using more clinical samples from both species as well as the functional role of antibodies specific to the novel conserved epitope identified in this study can be explored for protection against infection.